Synthesis of Depsipeptides via Isocyanide-Based Consecutive Bargellini–Passerini Multicomponent Reactions - Farhid, Hassan; Rostami, Mohammad Mahdi; Shaabani, Ahmad; Notash, Behrouz (SynOpen, 2021)
An efficient and straightforward approach has been established for the preparation of a new class of depsipeptide structures via isocyanide-based consecutive Bargellini–Passerini multicomponent reactions. 3-Carboxamido-isobutyric acids bearing an amide bond were obtained via Bargellini multicomponent reaction from isocyanides, acetone, and chloroform in the presence of sodium hydroxide. Next, via a Passerini multicomponent-reaction strategy, a new class of depsipeptides was synthesized using the Bargellini reaction products, isocyanides, and aldehydes. The depsipeptides thus prepared have more flexible structures than their pseudopeptidic analogues.
Keywords: depsipeptide; Passerini reaction; isocyanide